Arterial pressure suffices to increase liver stiffness - Piecha, Felix; Peccerella, Teresa; Bruckner, Thomas; Seitz, Helmut K.; Rausch, Vanessa; Mueller, Sebastian (American journal of physiology. Gastrointestinal and liver physiology, 2016)
Noninvasive measurement of liver stiffness (LS) has been established to screen for liver fibrosis. Since LS is also elevated in response to pressure-related conditions such as liver congestion, this study was undertaken to learn more about the role of arterial pressure on LS. LS was measured by transient elastography (μFibroscan platform, Echosens, Paris, France) during single intravenous injections of catecholamines in anesthetized rats with and without thioacetamide (TAA)-induced fibrosis. The effect of vasodilating glycerol trinitrate (GTN) on LS was also studied. Pressures in the abdominal aorta and caval and portal veins were measured in real time with the PowerLab device (AD Instruments, Dunedin, New Zealand). Baseline LS values in all rats (3.8 ± 0.5 kPa, n = 25) did not significantly differ from those in humans. Epinephrine and norepinephrine drastically increased mean arterial pressure (MAP) from 82 to 173 and 156 mmHg. Concomitantly, LS almost doubled from 4 to 8 kPa, while central venous pressure remained unchanged. Likewise, portal pressure only showed a slight and delayed increase. In the TAA-induced fibrosis model, LS increased from 9.5 ± 1.0 to 25.6 ± 14.7 kPa upon epinephrine injection and could efficiently be decreased by GTN. We finally show a direct association in humans in a physiological setting of elevated cardiac output and MAP. During continuous spinning at 200 W, MAP increased from 84 ± 8 to 99 ± 11 mmHg while LS significantly increased from 4.4 ± 1.8 to 6.7 ± 2.1 kPa. In conclusion, our data show that arterial pressure suffices to increase LS. Moreover, lowering MAP efficiently decreases LS in fibrotic livers that are predominantly supplied by arterial blood.
First published June 10, 2016
Gesehen am 20.10.2020